The influence of audit quality, the use of information technology, management support, and the application of guidelines on the effectiveness of internal audit in preventing and detecting fraud in hospitals - Marwanto, Marwanto; Soepriyanto, Gatot (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the effect of internal audit quality, the use of information technology, management support, and the implementation of SPI guidelines on the effectiveness of internal audits in preventing and detecting fraud. Quantitative research using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method was conducted on 385 hospital internal auditors from all over Indonesia through online questionnaires filled out on Google Forms. The results of hypothesis testing with a Two-Tailed T-Test on the PLS-SEM inner model construct concluded that the variables of guideline implementation, audit quality, and management support have a significant influence on the effectiveness of internal audits in preventing and detecting fraud. The application of guidelines has a very high influence on the effectiveness of internal audits in preventing and detecting fraud at the structural level. Coefficient of Determination testing shows that the joint effect of audit quality, the use of information technology, management support, and the implementation of guidelines has a high effect on the effectiveness of internal audits in preventing and detecting fraud. This study provides practical implications for hospitals to improve audit quality, utilize information technology, enhance management support, and implement SPI organizational guidelines in the internal audit process to encourage internal audit effectiveness in fraud prevention and detection. Further research is expected to be developed by examining other factors that can affect the effectiveness of internal audits in preventing and detecting fraud.